A comparative study of silver nanoparticle dissolution under physiological conditions. Issue 12 (4th November 2020) - Steinmetz, Lukas; Geers, Christoph; Balog, Sandor; Bonmarin, Mathias; Rodriguez-Lorenzo, Laura; Taladriz-Blanco, Patricia; Rothen-Rutishauser, Barbara; Petri-Fink, Alke
Abstract : The dissolution and aggregation behaviour of silver nanoparticles under physiological conditions and in biologically relevant environments is investigated by exploiting their plasmonic properties. Abstract : Upon dissolution of silver nanoparticles, silver ions are released into the environment, which are known to induce adverse effects. However, since dissolution studies are predominantly performed in water and/or at room temperature, the effects of biological media and physiologically relevant temperature on the dissolution rate are not considered. Here, we investigate silver nanoparticle dissolution trends based on their plasmonic properties under biologically relevant conditions, i.e. in biological media at 37 °C over a period of 24 h. The studied nanoparticles, surface-functionalized with polyvinylpyrrolidone, beta-cyclodextrin/polyvinylpyrrolidone, and starch/polyvinylpyrrolidone, were analysed by UV-Vis spectroscopy, lock-in thermography and depolarized dynamic light scattering to evaluate the influence of these coatings on silver nanoparticle dissolution. Transmission electron microscopy was employed to visualize the reduction of the nanoparticle core diameters. Consequently, the advantages and limitations of these analytical techniques are discussed. To assess the effects of temperature on the degree of dissolution, the results of experiments performed at biological temperature were compared to those obtained at room temperature. Dissolution is often enhanced at elevated temperatures, but has to be determined individually for every specific condition. Furthermore, we evaluated potential nanoparticle aggregation. Our results highlight that additional surface coatings do not necessarily hinder the dissolution or aggregation of silver nanoparticles.